Ventral periaqueductal grey stimulation alters heart rate variability in humans with chronic pain. - Pereira, E; Lu, G; Wang, S; Schweder, P; Hyam, J; Stein, J; Paterson, D; Aziz, T; Green, A (2010)
BACKGROUND: The midbrain periaqueductal grey (PAG) area is important for both pain modulation and cardiovascular control via the autonomic nervous system (ANS). While changes in blood pressure dependent upon dorsal or ventral electrode positioning have been described with PAG deep brain stimulation (DBS), little is known mechanistically about the relationships between pain and cardiovascular regulation in humans. Heart rate variability (HRV) is an established measure of cardiovascular regulation, and an index of autonomic function. METHODS AND RESULTS: 16 patients undergoing DBS of the rostral PAG for chronic neuropathic pain were investigated post-operatively to determine whether PAG stimulation would alter HRV, and the subjects' perception of pain. Mean heart rate together with HRV, time and frequency domain measures, low frequency (LF) and high frequency (HF) power components of heart rate and the ratio of LF to HF were calculated before and during DBS. Ventral but not dorsal PAG DBS significantly decreased the ratio of LF to HF power (p<0.05, n=8) with HF power significantly increased. Changes in LF/HF ratio correlated significantly with subjective reporting of analgesic efficacy using a visual analogue score (VAS; gamma(2)=0.36, p=0.01, n=16). Diffusion tensor imaging and probabilistic tractography of 17 normal controls' seeding voxels from the mean ventral and dorsal PAG stimulation sites of the 16 patient cohort revealed significant differences between rostral tract projections and separate, adjacent projections to ipsilateral dorsolateral medulla. CONCLUSIONS: Ventral PAG DBS may increase parasympathetic activity to reduce pain via anatomical connections distinct from dorsal PAG DBS, which may act by sympathetic mechanisms.